The Effect of Long-Term Contraceptive Method Education on Increasing the Number of Acceptors in Women Workers in Oil Palm Plantations - Christyanni, Yuyun; Rahmawaty, Fetty (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Background: Strengthening family planning program services by delaying or reducing the percentage of pregnancies for couples of childbearing age, namely by using Long Term Contraceptive Methods that are more effective and efficient for the purpose of spacing births for more than three years or terminating pregnancies in couples who no longer wish to have more children. But unfortunately this contraceptive method is less desirable, especially for working women in oil palm plantations. One of the factors that affect the low number of users is a lack of communication, information and education. Objective: This study aims to determine the effect of Long Term Contraceptive Method education on increasing the number of acceptors of female workers in oil palm plantations. Method: Quasi-experimental research with a one group pre and post test design. The population is all WUS who work at PT. Mustika Sembuluh East Kotawaringin Regency numbered 556 people. The sample in this study were 40 respondents with inclusion criteria and purposive sampling which would be divided into 4 small groups. Data analysis used the McNemar test. Result: this study found that before the intervention only a small proportion chose the Long-Term Contraceptive Method, namely 11 respondents (27.5%) and after the intervention increased to 25 respondents (62.5%) with a significant difference p<0.001. Conclusion: Providing education is significant in improving Long-Term Contraceptive Methods.